Effectiveness of Teaching and Learning Process Based on Competency Curriculum and Influence on Student Skills Activation: Study on Students of the Makassar Tourism Polytechnic - wim winowatan; Jeanny Pricilia Anneke W (CV. Media Digital Publikasi Indonesia, 2023)
This study aims to obtain an empirical description of the skill level of students and whether there is a significant difference in the level of student skills before competency-based learning and after learning the competency-based curriculum at the Makassar Tourism Academy's Dish Management Study Program. This type of research is a survey with the independent variable being competency-based learning and the selection variable being the skill level of students using total sampling because the number of students studied was thirty people. Collecting data using observation techniques, namely by directly observing student skills, while the analytical technique used is T-test analysis (test difference between two averages). The results showed that the skill level of the students of the Dish Management Study Program at the Makassar Tourism Academy in competency-based learning was at a level that was less and less. On the other hand, after learning the competency-based curriculum, there was a significant increase, namely, they were at a good and very good level. Furthermore, there is a significant difference in the skill level of students before and after learning the competency-based curriculum in students of the culinary management study program. Based on the results of this study, it is suggested that the management of the Makassar Tourism Academy in the future can apply the learning process using a competency-based curriculum as has been implemented in several vocational schools in Indonesia. Implementation of Competency-Based Curriculum Learning is very helpful and improves students' skills